Victim identification in large-scale disasters using dental findings. (July 2019) - Hajime Utsuno, D.D.S.
Abstract: Recently, personal identification based on dental findings (PIDF) has been proven to be a useful and accurate technique. This approach involves the treatment of the 5 surfaces of the 32 teeth in adults. The rate of mismatch between a target an individual is significantly low in the event of multiple dental treatments. In some cases, an individual may be recognized based on their morphological features without the need for dental analysis. PIDF has proven to be highly effective when human remains are unidentifiable e.g. skeletal, decomposed, burned and partial remains, etc. However, if the features of a victim are recognizable, identification should be performed based on facial feature or fingerprints. PIDF is particularly useful when there is a heavy toll on human lives. A large-scale disaster is a typical case for the application of this method. In this report, the utility of PIDF and their application are presented using geographic and Japanese domestic transportation cases. Highlights: This paper presents the relationship between large-scale disasters and accidents related to vehicles. The term "disaster" is defined and categorized into open and close disaster with explanation. Dental identification with simplified anatomy is introduced. Two large-scale disaster cases that occurred in Japan are introduced.